Relationship between the early Boceprevir-S isomer plasma concentrations and the onset of breakthrough during HCV genotype 1 triple therapy. (February 2015) - Boglione, L.; De Nicolò, A.; Cardellino, C.S.; Ruggiero, T.; Ghisetti, V.; Cariti, G.; Di Perri, G.; D'Avolio, A.
Abstract: In a prospective cohort of 18 patients treated with boceprevir, we examined the role of boceprevir plasma concentration at the onset of breakthrough during the treatment. Nine patients experienced breakthrough during therapy. The resistance patterns were as follows: S122S/R, I132V, T54A/I132V, V156S/I170A, V36M/T54S/R155K, V36M/R155K and T54/R155K. Boceprevir-S isomer (SCH 534128) median concentration in patients with breakthrough was 48.3 ng/mL (interquartile range 43–58 ng/mL); in others, it was significantly (p 0.019) higher: 151 ng/mL. Low boceprevir plasma concentration can lead to virologic resistance; therapeutic drug monitoring should be used to prevent the onset of viral breakthrough during triple-regimen therapy with boceprevir.